IMPLEMENTATION OF BASIC TEACHING MATERIALS IN THE STUDENTS OF FACULTY OF EDUCATION AND SCIENCE AT PAMULANG UNIVERSITY - Rusmaini, Rusmaini; Soffiatun, Soffi (CV. Pena Persada, 2019)
One of the interesting focuses and issues to be studied from education are teach how tomaterial and how to teach a teacher. The use of teaching materials can be used as abenchmark in the learning process. The subjects of this study were students andlecturers of economic education FKIP Pamulang University. This research wasconducted using the Research and Development (R&D) research method. The results ofthe study showed that students needed teaching materials that were in accordance withtextbook eligibility standards which included (1) the feasibility of the contents of thematerial, (2) the feasibility of the presentation, (3) the linguistic feasibility, and (4) thefeasibility of the graphics. From the results of the t-test data processing it is known thatthe t value of (10.379)> t table value (0.679) with a significance level (sig) of 0.000 sothat it can be concluded that there are a significant differences between the averagevalue of students before and after teaching practice with use teaching materials BasicTeaching Skills. Therefore, these teaching materials are effective and accepted.